Computational Phenotypes: Where the Theory of Computation Meets Evo-Devo - Sergio Balari; Guillermo Lorenzo (Biolinguistics, 2009)
This article argues that the Chomsky Hierarchy can be reinterpreted as a developmental morphospace constraining the evolution of a discrete and finite series of computational phenotypes. In doing so, the theory of Morphological Evolution as stated by Pere Alberch, a pioneering figure of Evo–Devo thinking, is adhered to.